Elaboración y comercialización de abonos orgánicos a través de la creación de una procesadora en el cantón pueblo viejo de la provincia de los Ríos - Suárez Morante, Sandra Leonela Suárez Morante (2015)
This study of skills and competencies is to find the relationship management system and aims to find the relationship made by small businesses. This study focuses on the development of practical knowledge to find related capabilities. Variables associated with the design skills and competencies to carry out a descriptive analysis by determining what we want to achieve are identified.